1968
DOI: 10.1515/znb-1968-0112
|View full text |Cite
|
Sign up to set email alerts
|

Messung der T-Fixierung bei einigen Teilschritten der Glykolyse

Abstract: On the irreversible conversion of glucose-6-phosphate to fructose-6-phosphate in H2O/HOT with glucose-6-phosphate-isomerase 8 - 10% of the tritium content per gram atom hydrogen in the water are incorporated. The corresponding figures for the enzymatical conversions of mannose-6-phosphate → fructose-6-phosphate, dihydroxyacetone phosphate → glyceraldehyde phosphate, phosphoenol pyruvate → pyruvate are 17 - 18, 15 and 16% respectively. When fructose-l,6-diphosphate is transferred into dihydroxyacetone phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…Figure 2 shows the maximum velocities from pH 6 to 9 in H20 and D20 and the extent of discrimination against 3H from the medium in both cases. As reported previously (Simon et al, 1968;Robinson & Rose, 1972), a 6-8-fold discrimination against 3H is seen in H20. This can only occur if 3H that is not used in the ketonization step is able to exchange into the medium or exchange with of the donor.…”
Section: Resultssupporting
confidence: 84%
“…Figure 2 shows the maximum velocities from pH 6 to 9 in H20 and D20 and the extent of discrimination against 3H from the medium in both cases. As reported previously (Simon et al, 1968;Robinson & Rose, 1972), a 6-8-fold discrimination against 3H is seen in H20. This can only occur if 3H that is not used in the ketonization step is able to exchange into the medium or exchange with of the donor.…”
Section: Resultssupporting
confidence: 84%
“…It is doubtful if less than 10% of transfer would have been detected. Simon and his collaborators (Simon et al, 1968), using o-[3-3H]glucose, hexokinase, phosphoglucose isomerase, phosphofructokinase, and aldolase to prepare specifically labeled dihydroxyacetone phosphate in situ, reported that some 10% of the 3H in dihydroxyacetone phosphate was transferred intramolecularly to glyceraldehyde phosphate in the isomerase-catalyzed reaction. The validity of this experiment depends, inter alia, on the isotopic purity of the tritiated glucose, and Dr. Simon has recently informed us that because some 5% of the 3H label on the starting glucose was in the 6 position, the revised estimate of the extent of tritium transfer (from dihydroxyacetone phosphate to glyceraldehyde phosphate) in the yeast isomerase-catalyzed reaction is about 5% at pH 8.7.…”
Section: Discussionmentioning
confidence: 99%
“…Xhe triose-P isomerase catalyzed reaction is generally believed to proceed through a ris-enediol intermediate as shown in Scheme I,1 i.e., a simple proton abstraction and transfer by a single base believed to be a glutamate. Proton, rather than hydride, transfer is strongly inferred in the TIM reaction from the observation that the substrate-derived tritium is largely exchanged for a medium proton (Reider & Rose, 1959; Simon et al, 1968;Maister et al, 1976) and by the slow formation of Pj and methylglyoxal, indicative of an enediol-P on the enzyme (Browne et al, 1976;Richard, 1984).…”
mentioning
confidence: 99%